Optimization of goods relocation in urban store networks with an incentive strategy - Bartolomeo Silvestri; Michele Roccotelli; Raffaello Pio Iavaniglio; Luigi Ranieri (IET Collaborative Intelligent Manufacturing, 2021)
Abstract Nowadays, goods are relocated daily among urban fashion stores by van or truck. This relocation activity generates externalities in urban areas that cause deterioration in the quality of life of their citizens. Innovative strategies based on a sharing approach promise solutions to reduce the use of heavy, polluting vehicles and therefore the related externalities in urban areas. The authors aim to optimise the relocation activity of city fashion stores through a customer‐involved incentive mechanism. The method provides store shopping vouchers to loyal customers as a reward for package delivery from one shop to another. If no customers agree to participate in the delivery game, company relocation staff will perform the delivery service. The benefit of the proposed delivery game is twofold—it increases customer loyalty and reduces the externalities produced by heavy vehicles moving through the city. To this end, two integer linear programming problems are formalised to optimise goods relocation activity with package deliveries (1) by company staff only and (2) by loyal customers in an incentive game. A simulation case study is presented to show the application of the methodology in fashion stores.